Advanced Technology and Changes in Labor Demand in Russia - Olga KOROPETS1; Evgeniya TUKHTAROVA2; Natalya NEKLYUDOVA2 (Communications of International Proceedings, 2020)
The article presents the impact analysis of the widespread use of advanced technologies on unemployment in the Russian regions. The authors believe that the transition to a new technological order, will restructure the labor demand in the regional labor markets of Russia. This restructuring will raise the demand for blue-collar workers, while those with university education will experience problems with employment. To confirm the proposed thesis, the authors used a correlation-regression analysis of space-time series. The study shows that most Russian regions have low potential for the new technological order transition. The use of this method allowed the authors to record a trend towards a decrease in the demand for people with university degrees, but also a significant difference between the regions towards the transition to the new technological order. Thus, the analysis results showed that high-tech regions with sufficient potential for the new technological order do not need a large number of people with higher education. At the same time, under the new conditions, high-tech regions are experiencing an acute shortage of workers with a secondary professional vocational education.
Keywords: Unemployment; Industry 4.0; Level of Education; Higher Education; Secondary Professional Education; Complete Secondary Education; High-Tech Regions